Management of Tricky Lymphoma Cases - Kitay, Alice Miriam; Chaloupka, Karla (Klinische Monatsblätter für Augenheilkunde, 2022)
Lymphoma lesions are frequent, but their appearance may differ. We discuss aspects that are not to be overlooked. We present seven cases (aged 40 – 93 years) with unexpected lymphoma findings, demonstrating a vast variability of history, clinic, and management. A lymphoma can progress over years, either imitating dermatochalasis or rapidly resembling an abscess. Correlation between clinic, imaging, intraoperative setting, and carefully chosen spot of biopsy are crucial. A simple subconjunctival biopsy may be sufficient in a retrobulbar lesion. We emphasize that an early biopsy is essential and that its location must be carefully considered. Individual management is based on history and systemic findings.
Keywords: lymphoma; oculoplastic surgery; biopsy; diagnostic imaging